TRENDS OF TOURISM DEVELOPMENT IN THE MODERN WORLD - Abysova, Mariia; Saladis, Inna (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2022)
Introduction. The scale and pace of social changes during the pandemic actualizes the socio-philosophical analysis of trends in tourism as one of the most dynamically developing social institutions. The aim is socio-philosophical analysis of the main trends in tourism in the modern world. The tasks are: 1) to to study the determinants of the development of the institute of tourism in the modern world; 2) to identify the features of changing the role and place of the institute of tourism in the quarantine restrictions of modern society.Research methods used in the article are systemic, institutional approach, structural and functional analysis, problem method, method of expert assessments, generalization, content analysis. Research results. The conditions tourism develops in are influenced by numerous factors. The most important external factors are natural (cataclysms, pandemics, etc.), political and socio-economic ones. In addition to them, there are phenomena and trends that are manifested directly in the field of tourism, namely: the demand and supply of tourist services; institutional and technical-technological factors. In the context of globalization of the tourism market, the role and importance of the quality of information exchange in the tourism market is growing. The information technologies used in the modern tourism business can be divided into two groups. The first group includes technologies that promote automation and increase the efficiency of internal office business processes. The second group provides interaction with the end user. Discussion. In addition to the development of the main areas of tourism, in parallel, the dominant trend in the development of world tourism is the formation and development of the tourism industry as an industry of impressions. Conclusion. The development of tourism is influenced by external (natural, economic, political) and internal (related to the demand and supply of tourist services, institutional and technical-technological) factors. The coronavirus pandemic and the accompanying anti-epidemic measures have called into question the profitability of the industry, millions of job places, but have differentiated the forms of tourism, approving the trend towards an individualized tourism product. The globalization of the tourism sector as a consolidation and active penetration of the capital of individual companies in foreign tourism markets by merging or absorbing the spheres of tourism service has contributed to the establishment of a single information exchange between its participants. The tourist market offers are changing to alternative and non-traditional ones. The transition to the impression industry determines the increase in demand for exotic types of tourism and requires the creation of a new tourism product suits the ever-changing needs of tourists.